Analysis of characteristics and causes of child road traffic death (CRTD) of China in 2013 - Jihong Zhou (3120027) (2015)
Objective To study the mortality, causes and characteristics of child road traffic death (CRTD) in China in 2013, in order to find new ways to improve CRTD prevention and control. Materials: The road traffic death data and population data of children under 18 years old in 2013 were mainly from: (1) Annual statistics report on road traffic accident of China in 2013, by Transportation Bureau, Ministry of Public Security. (2) Annual demographic data by China State Statistics Bureau. Results CRTD were 3994 persons and the ratio of male and female was1.64:1 in 2013. The highest CRTD occurred in 15-17 years old group which was 30.0% of total, followed by 2-5 years old group (28.3%). Mortality per million population (MPMP) of total CRTD was 14.61 persons. The highest MPMP was 23.92 persons in 15-17 years old group. MPMP of male was 16.85 persons, and the highest group was 15-17 years old group with MPMP 33.30 persons. MPMP of female was 11.99 persons, and the highest group was 2-5 years old group with MPMP 16.54 persons. The highest ratio of male and female was in 15-17 years old group(2.47:1). However, female was much more than male in 0-1 years old group (0.76:1). Brain injury was the main cause of CRTD (78.1%), followed by chest and abdomen injury (8.8%). This paper has also deeply studied on the crash reasons, part of injury, time distribution and so on about CRTD in 2013. Conclusion The CRTD of high school and preschool children were highlight in all groups, and it was very remarkable that CRTD of female was much more than that of male in 0-1 years old group. Brain injury is the main cause of death. Cause of accident and death, injury part, gender, transportation mode and time distribution all have different characteristics in different groups. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.48